Research progress of sophoridine’s pharmacological activities and its molecular mechanism: an updated review - Chen, Yiwei; Wang, Xiang; Ye, Dongmei; Yang, Zhousheng; Shen, Qingrong; Liu, Xiaoxia; Chen, Chunxia; Chen, Xiaoyu (Frontiers in Pharmacology, 2023)
Sophoridine, the major active constituent of Sophora alopecuroides and its roots, is a bioactive alkaloid with a wide range of pharmacological effects, including antitumor, anti-inflammatory, antiviral, antibacterial, analgesic, cardioprotective, and immunoprotective activities. Its antitumor activity is particularly remarkable, as it can inhibit cancer cell proliferation, invasion, and metastasis while inducing cell cycle arrest and apoptosis. Additionally, sophoridine also holds therapeutic potential for myocardial ischemia, osteoporosis, arrhythmias, and neurological disorders, primarily through the suppression of related inflammatory factors and cell apoptosis. However, sophoridine has also exhibited adverse effects such as hepatotoxicity and neurotoxicity. The antidisease effect and mechanism of sophoridine are diverse, so it hashigh research value. This article focuses on summarizing the pharmacological mechanisms of sophoridine, discussing its toxicity and derivatives, and proposing future research directions for sophoridine.